PLATOOL: A Functional Test Generation Tool for Mobile Applications - Marinho, Euler Horta; Figueiredo, Eduardo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Mobile applications are ubiquitous nowadays and their testing is a central activity for quality assurance. Software testing is considered an important activity in this context. Application testers are faced with several classes of events in this domain including GUI and system events, such as sensor-related events. While GUI events have been systematically explored in mobile application testing literature, system events have received less attention. A possible difficulty faced by mobile application testers is the identification and generation of input data for system events. This paper presents PLATOOL for assisting mobile application testers to deal with common events of the mobile applications during the automation of functional tests. Our preliminary results indicate that PLATOOL is able to generate and execute useful functional tests to support testing of mobile applications.